Causal Pathways from Body Components and Regional Fat to Extensive Metabolic Phenotypes: A Mendelian Randomization Study. Issue 8 (22nd July 2020) - Si, Shucheng; Tewara, Marlvin Anemey; Li, Yunxia; Li, Wenchao; Chen, Xiaolu; Yuan, Tonghui; Liu, Congcong; Li, Jiqing; Wang, Bojie; Li, Hongkai; Hou, Lei; Wang, Qing; et al.
Abstract : Objective: The aim of this study was to explore the causal effects and pathways from body components to extensive metabolic phenotypes. Methods: Summarized data including 24 metabolic phenotypes from 10 consortiums were used to perform univariate, multivariable, and bidirectional Mendelian randomization analysis based on the network design. Results: For metabolically related biomarkers, a 1‐SD increase in body fat mass (BFM) was robustly associated with increased fasting insulin, systolic blood pressure, diastolic blood pressure, and urate and decreased high‐density lipoprotein cholesterol levels. For metabolically related diseases, the odds ratios and 95% CIs of a 1‐SD increase in BFM were 1.76 (1.37 to 2.25) for type 2 diabetes mellitus (T2DM), 1.11 (1.09 to 1.13) for hypertension, 1.40 (1.25 to 1.57) for coronary artery disease, 1.41 (1.25 to 1.59) for myocardial infarction, 1.25 (1.12 to 1.40) for ischemic stroke, and 1.62 (1.02 to 2.57) for gout. The effects of body fat on diseases were mediated by extensive intermediate biomarkers, including blood pressure, lipids, glycemic traits, and urate. Regional fats had a similar effect with body fat in both absolute and relative scales, whereas fat‐free components increased only the risk of T2DM 1.73 (1.11 to 2.68) and chronic kidney disease 1.51 (1.11 to 2.06). Conclusions: Several potential pathways were found and confirmed the tremendous benefits of fat‐lowering measures, including lowering of various regional fats. Future policies or interventions should focus more on the role of body fat.